Rubber compounds from pilot‐scale supercritical carbon dioxide assisted devulcanized rubber: Curing characteristics, mechanical and thermal properties - Sangit Paul; Manjur Rahaman; Suman Kumar Ghosh; Ankur Katheria; Narayan Ch. Das (SPE Polymers)
Abstract Recycling scrap tires is currently the most significant approach for promoting environmentally friendly production and consumption on an industrial scale. The cross‐linked sulfur bonds in scrap tires are broken during the devulcanization process. According to most of the literature, laboratory‐scale types of equipment were utilized for the studies on supercritical carbon dioxide (scCO2) for devulcanizing scrap tires. However, significant pilot‐scale research and a thorough examination of product reusability are essential to be broadly embraced as a feasible alternative for commercial application. Pilot‐scale supercritical fluid extraction equipment was used in this study to devulcanize crumb rubber obtained from discarded tires. The devulcanization treatment involved utilizing scCO2 and diphenyl disulfide (a decrosslinking agent). The trial adopted optimum process conditions achieved by the Taguchi‐DEAR design of experiments approach to generate devulcanized rubber. The devulcanized rubber is then re‐vulcanized with varying sulfur concentrations ranging from 1 to 2.5 phr. The re‐vulcanized rubber composites are examined by tensile test, dynamic mechanical analyzer, thermogravimetry analysis, and differential scanning calorimetry analysis. Morphology and surface roughness of composites are assessed through field emission scanning electron microscope and atomic force microscope, respectively. The optimal sulfur dose for re‐vulcanization is determined to be 1.5 phr depending on the curing, mechanical, and thermal characteristics of the composites. The lower crosslink density of the re‐vulcanized composites signifies that all crosslink sites are not accessible during the re‐vulcanization process, which can be addressed by employing other curing techniques. At the end, the study investigated the probable devulcanization and re‐vulcanization reaction mechanism. Highlights Thermochemical devulcanization of the waste tire in a pilot‐scale setup. Utilization of CO2 as a supercritical solvent and diphenyl disulfide as a decrosslinking reagent. Vulcanization of devulcanized rubber using sulfur accelerator curing system. Morphological, mechanical, and thermal properties assessed of rubber composites.